Gaultheria longibracteolata R. C. Fang (Ericaceae Juss.) a new record species for the flora of Vietnam - Thanh Huong, Nguyen Thi; Hiep, Nguyen Tien (Academia Journal of Biology, 2012)
The genus Gaultheria L. (Ericaceae Juss.) comprises approximately 135 species, distributed in SE Asia, SE Australia, North and South America, Pacific Islands. Specimens of Gaultheria longibracteolata have been found in Lao Cai and Yen Bai provinces as a new record for the flora of Vietnam. Thus there are 6 species belonging to the genus Gaultheria L. recorded in Vietnam. This species differs from others known in Vietnam by twig densely brown hispid and puberulous, flowers numerous, calyx lobes oblong, corolla urceolate.